Antimicrobial Resistance & Infection Control - Stewardson, Andrew; Vandenbroucke-Grauls, Christina; Tschudin Sutter, Sarah; Whitelaw, Andrew; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Antimicrobial Resistance and Infection Control is an open access, peer-reviewed journal that focuses on the prevention of healthcare-associated infections and antimicrobial resistance. This is accomplished through the publication of innovative, high-quality original research from low-, middle-, and high-income countries. The journal welcomes submissions from the broad field of healthcare epidemiology and infection prevention and control. While the journal$1 (Bs primary focus is on infection prevention in healthcare, submissions from other fields or settings (e.g., public health, One Health, or antimicrobial stewardship) will also be considered where these relate directly to the prevention of antimicrobial resistance or healthcare-associated infections in humans. Given the stated aims and scope, the journal does not routinely consider submissions relating to the following topics: Single-point and single-centre estimates of antimicrobial resistance rates, unless they illustrate new developments of broad interest to those working in healthcare epidemiology and infection prevention. Animal health or the environment, unless these explore a direct relationship to human health (One Health principle). Clinical diagnosis or treatment of infectious diseases. Laboratory-based research and microbiological/genomic aspects of AMR without implications for clinical infection prevention. .s
Keywords: Medical microbiology; Diseases; Medical Microbiology; Diseases